CALCULATION AND MODELING OF EMISSIONS FOR SOLID AND LIQUID FUELS - Spriņģe, Zaiga; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The thesis contains information on emissions and their calculations and formulas. Information about and working with ADMS Screen was reviewed. The results obtained using this program were summarized in tables and emission dispersion schedules were obtained. The information obtained was analyzed and conclusions were drawn.